Subtalar Arthrodesis Union Rates With and Without Adjacent Ankle Arthrodesis. (October 2022) - Jennison, Toby; Dalgleish, James; Taher, Suhib; Chadwick, Carolyn; Blundell, Chris; Davies, Mark; Davies, Howard
Background: Subtalar arthrodesis is the surgical procedure commonly performed to treat subtalar arthritis. Subtalar arthrodesis may have a higher nonunion rate if there is a preexisting adjacent joint arthrodesis. The aim of this retrospective cohort study was to compare the subtalar arthrodesis union rate of patients with native tibiotalar joints to that of patients with prior tibiotalar arthrodesis. The secondary aim was to assess risk factors for nonunion. Methods: A retrospective cohort study of consecutive patients that underwent a subtalar arthrodesis in a single center between 2010 and 2020. The primary outcome of union was determined based on bridging callus on radiographs and clinical symptoms. If there was uncertainty, then a nonweightbearing CT was acquired. Chi-squared test and Mann-Whitney tests compared differences in demographics and risk factors for nonunion between groups. A logistical regression model was performed to determine risk factors for nonunion. Results: Eighteen patients had an adjacent ankle arthrodesis and 53 patients did not. The successful subtalar arthrodesis union rate in those with a preexisting ankle joint arthrodesis (44.4%) was approximately half that in those without an ankle joint arthrodesis (86.8%) ( P < .001). On multivariate logistic regression, an adjacent ankle arthrodesis was the only significant risk factor for nonunion. The odds ratio of nonunion of the subtalar joint with an adjacent ankle arthrodesis present was 4.90 (95% CI 1.02-23.56) compared to a subtalar arthrodesis with a native ankle joint. In addition, 9.4% of patients without an ankle arthrodesis underwent a revision subtalar arthrodesis compared with 44.4% of those with an adjacent ankle arthrodesis ( P = .001). Conclusion: In our study, we found that patients undergoing a subtalar arthrodesis with an adjacent ankle arthrodesis have a significantly increased risk of nonunion compared with those undergoing a subtalar arthrodesis with a native ankle. Patients with a previously fused ankle need counseling about the high risk of nonunion and potential additional surgery.